Composite Blastoid Variant of Mantle Cell Lymphoma and Classical Hodgkin Lymphoma. (May 2017) - Murray, Ciara; Quinn, Fiona; Illyes, Gyorgy; Walker, Jan; Castriciano, Giussepa; O'Sullivan, Paul; Grant, Cliona; Vandenberghe, Elisabeth; Bird, Brian; Flavin, Richard
Composite lymphoma (CL) describes the rare occurrence of 2 or more distinct types of lymphoma in a single anatomical location. We present the case of a 78-year-old man presenting with a 3-month history of weakness, malaise, and increasing dyspnea. A lymph node excised from the posterior triangle of the neck revealed the coexistence of 2 morphologically and phenotypically distinct lymphoid neoplasms consistent with a blastoid variant of mantle cell lymphoma (MCL) occurring in composite with classical Hodgkin lymphoma (cHL), mixed cellularity subtype. A t(11;14)(q13;q32) translocation was demonstrated by fluorescence in situ hybridization in the MCL and Hodgkin Reed-Sternberg cells of the cHL. Multiplex polymerase chain reaction detected clonal Immunoglobulin heavy chain (VFR1-J, VFR2-J, and VFR3-J), clonal immunoglobulin light chain kappa (V-J and V/JC intron-kde) and clonal immunoglobulin light chain lambda (V-J) gene rearrangements in the MCL. This report represents the first case of a blastoid variant of MCL occurring in composite with cHL.